Utilization of varenicline among Kansas Medicaid enrollees - Nathalia M. Machado; Aaron J. Katz; Kimber P. Richter; Edward F. Ellerbeck (PLoS ONE, 2025)
Background Smoking prevalence among Medicaid beneficiaries is twice that of privately insured adults, yet effective smoking cessation treatments remain underutilized. Understanding varenicline use, the most effective smoking cessation medication, can inform efforts to improve tobacco treatment for Medicaid enrollees. Objectives To describe varenicline utilization among Kansas Medicaid (KanCare) enrollees from 2014–2021, including changes related to the FDA’s December 2016 removal of the black box warning, and explore changes and demographic differences in its use. Research design This retrospective cohort study analyzed pharmacy claims data for varenicline utilization from January 1, 2014, to December 31, 2021. Tobacco use was estimated from the KanCare External Quality Review survey. Subjects The sample included 78,295 new adult enrollees (age 18+) with at least 11 months of continuous coverage. Measures The primary outcome was varenicline utilization, defined as any pharmacy claim for the medication. Secondary outcomes included time to first prescription, completion of the 12-week treatment, and demographic differences in use. Results With an estimated 30% smoking prevalence, only 12.7% of KanCare smokers received varenicline, and just 1.6% completed a full course of treatment. Among 78,295 new enrollees, 2,980 (3.8%) had one or more claims for varenicline, with the mean time from enrollment to first prescription being 1.5 years (SD 1.3). Utilization was higher among males (4.8%) than females (3.4%) and varied by race/ethnicity (Whites: 4.4%, Blacks: 2.7%, American Indians: 2.5%, Hispanics: 1.6%, p<0.0001). Among those who initiated treatment, only 13.5% (N=380) completed the recommended 12-week regimen., Conclusions Despite the high smoking prevalence among KanCare beneficiaries, varenicline is underutilized, with significant demographic disparities. Men and non-Hispanic Whites were more likely to receive varenicline than women and other racial and ethnic groups, despite comparable or higher smoking rates among other subgroups. Medicaid programs must intensify efforts to provide equitable and effective tobacco treatment.